DAMPAK KEBERADAAN TAMAN NASIONAL SIBERUT (TNS) TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DESA SIMATALU (1993-2012) - Herman, Riki; Erawati, Meri; Kharles, Kharles (Pendidikan Sejarah, 2014)
This research aims to determine how the effects of the presence of Siberut National Park to the socio-economic life of the village community Simatalu . since the enactment of Siberut Island as a national park in 1993 result existence of two conflicting things between economic needs with conservation efforts . This study uses historical research meteode namely : (1) heuristic , (2) internal and external criticism , (3) interpretation and (4) the stage of writing a thesis result . the results showed that the presence of a national park in the village Simatalu since 1993-2012 are : (1) . The existence Siberut National Park as a form of a forest conservation movement from extinction as a support for the viability of the surrounding habitat . Siberut National Park was formed based because of the existence of a unique point on the island , both in terms of its forests are so vast plus it is supported by a wide variety of endemic species that are owned and supported by the lives of the people who have the unique culture that should be preserved . (2) . Simatalu rural life is always dependent on the natural surroundings without the control that is bound to make forests will become extinct and thus peoples lives will also be disrupted . Therefore, the establishment of the National Park in 1993 to give more control to people who live directly adjacent to the forest . (3) . Existence of National Parks in the area Simatalu make a change towards a better economy , but in terms of advancing the economic life of society can not be denied will result from threatened forests . This possibility can not be avoided because of the efforts in improving peoples lives depend on the surrounding forest . Nonetheless been an increase in the standard of living in the community perceived social skills , social status can at least be better than ever . The existence a national park in the village Simatalu not closed the possibility of changes in population density and social life at a better level. People who are not used to interact with the outside society is now open access to interact.Â Keyword: impact of the National Park